Environment-friendly two-component polyurethane heat-conducting structural adhesive and preparation method thereof
By preparing an environmentally friendly two-component polyurethane thermally conductive structural adhesive, the harm of organic volatile solvents in existing adhesives to the environment and human health is solved, and an efficient thermal conductivity, good mechanical properties and environmentally friendly adhesive is achieved.
Patent Information
- Application Number
- CN202411617385.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-07
AI Technical Summary
When existing adhesives are used in power batteries, in order to dissolve high molecular weight polymers and adjust viscosity, organic volatile solvents are often added, which is harmful to the environment and human health.
An environmentally friendly two-component polyurethane thermally conductive structural adhesive, including components A and components B, is provided to make component A by using polyether diol, polyaspartate resin, silane coupling agent and thermal filler , component B is prepared using polyurethane prepolymer and thermal filler, and polyurethane prepolymer is prepared by cross-polymerization of bio-based polyol and diisocyanate.
This adhesive has excellent thermal conductivity, mechanicality, sustainability and fluidity, low VOC emissions and no solvents, which is conducive to environmental protection and is suitable for filling and protection of new energy power batteries.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and in particular relates to an environmentally friendly two-component polyurethane thermal conductive structural adhesive and a preparation method thereof. Background Art
[0002] With the rapid development of the global economy and the firm push to achieve "carbon neutrality", the new energy vehicle industry is developing strongly. New energy electric vehicles are at the forefront of solving energy and environmental challenges and alleviating urban traffic congestion, and are expected to become the main focus of the future development of the automotive industry. It is generally recognized that the power battery is the "heart" of new energy vehicles, and adhesives are considered to be the lasting power of this "heart", ensuring its "myocardial vitality".
[0003] In power batteries, adhesives are mainly used for structural bonding, anti-vibration and thermal management. Therefore, battery factories and new energy vehicle manufacturers have a high demand for adhesives that are moisture-proof, highly elastic, have high bonding strength, and are highly heat-conductive while remaining cost-effective. Thermally conductive structural adhesives provide a solid solution for cell injection in new energy vehicle power battery packs, effectively providing filling and protection, and promoting timely heat dissipation.
[0004] However, in order to dissolve high molecular weight polymers and adjust viscosity, organic volatile solvents are often added to adhesives, which is harmful to the environment and human health. Today, the concept of green chemistry is widely and deeply rooted in the public consciousness. With the development of this trend, solvent-based adhesives are gradually being replaced by solvent-free alternatives, mainly because solvent-based adhesives release harmful volatile organic solvents (VOCs). Solvent-free polyurethane adhesives fundamentally eliminate solvent residues and reduce production costs, which is in line with the "dual carbon" goal and is the focus of the sustainable low-carbon development strategy. Summary of the invention
[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides an environmentally friendly two-component polyurethane thermal conductive structural adhesive and a preparation method thereof. The specific technical scheme is as follows:
[0006] The first object of the present invention is to provide an environmentally friendly two-component polyurethane thermal conductive structural adhesive, comprising the following components in parts by weight:
[0007] Component A: 5-10 parts of polyether diol, 15-30 parts of polyaspartic acid ester resin, 1-2 parts of silane coupling agent, 60-70 parts of thermal conductive filler;
[0008] Component B: 30-40 parts of polyurethane prepolymer and 60-70 parts of thermal conductive filler; the polyurethane prepolymer is a polymer with NCO terminal;
[0009] The volume ratio of the A component to the B component is 1:1.
[0010] The polyaspartic acid ester resin used in the present invention has the characteristics of high solid content (90%-100%) and low VOC (volatile organic compound) emission, which is beneficial to environmental protection.
[0011] Furthermore, the polyurethane prepolymer is prepared from the following components in parts by weight: 35-75 parts of bio-based polyol, 15-55 parts of diisocyanate, and 5-10 parts of plasticizer.
[0012] The present invention adopts bio-based polyol and diisocyanate cross-linking polymerization and strictly controls the amount of each material and the molar ratio of the group, so that the prepared polyurethane prepolymer has excellent environmental sustainability and fluidity.
[0013] Furthermore, the molar ratio of isocyanate groups to hydroxyl groups in the polyurethane prepolymer is 2.5-3.0:1.
[0014] Furthermore, the preparation method of the polyurethane prepolymer is as follows: diisocyanate is heated to 50-70°C under a N2 atmosphere with mechanical stirring, and then a mixture of bio-based polyol and plasticizer is slowly dripped in, and the dripping time is controlled at 0.8-1.2h. The mixture is reacted for 4-6h under N2 protection at a temperature of 80-85°C, and then cooled to room temperature when the NCO value does not change, to obtain a light yellow transparent polyurethane prepolymer.
[0015] Furthermore, the bio-based polyol is at least one of castor oil polyol, soybean oil polyol, palm oil polyol, and rapeseed oil polyol, preferably castor oil polyol; the diisocyanate is at least one of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate, preferably isophorone diisocyanate; and the plasticizer is 2-acetylcitrate tributyl.
[0016] Furthermore, the polyether diol is at least one of polyoxypropylene diol and polytetrahydrofuran diol, preferably polytetrahydrofuran diol.
[0017] Furthermore, the polyether diol has a hydroxyl value of 50-500 mg KOH / g, an average hydroxyl molecular weight of 250-2000, and an acid value of less than 1.
[0018] Furthermore, the molecular weight of the polyaspartic acid ester resin is 554-660, and the equivalent weight is 277-330 g / mol.
[0019] Furthermore, the silane coupling agent is one of KH-550, KH-560, KH-570, and KH-792, preferably KH-792.
[0020] Furthermore, the thermally conductive filler is at least one of aluminum oxide, magnesium oxide, zinc oxide, aluminum nitride, boron nitride, silicon carbide, and a composite of aluminum oxide and boron nitride, preferably a composite of aluminum oxide and boron nitride.
[0021] The second object of the present invention is to provide a method for preparing the above-mentioned environmentally friendly two-component polyurethane thermally conductive structural adhesive, comprising the following steps:
[0022] (1) placing polyether diol, polyaspartic acid ester resin, silane coupling agent and thermal conductive filler into a stirring kettle and evacuating and stirring for 1-2 hours, with the mixing temperature being ≤60°C and the vacuum degree being -0.08-0.09MPa, to obtain component A;
[0023] (2) Put the polyurethane prepolymer and thermal conductive filler into a stirring kettle, evacuate and stir for 1-2 hours, the mixing temperature is ≤50°C, and the vacuum degree is -0.08-0.09MPa, to obtain component B.
[0024] The beneficial effects of the present invention are:
[0025] The environmentally friendly two-component polyurethane thermally conductive structural adhesive prepared by the present invention includes component A and component B. The two components can be mixed when used. It has excellent thermal conductivity, mechanical properties, sustainability and fluidity, low VOC emissions, does not contain solvents, is beneficial to environmental protection, and is suitable for filling and protecting new energy power batteries. DETAILED DESCRIPTION
[0026] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0027] Embodiment 1:
[0028] Preparation of an environmentally friendly two-component polyurethane thermal conductive structural adhesive:
[0029] 1. Preparation of polyurethane prepolymer
[0030] Weigh 283g of isophorone diisocyanate into a 2000ml three-necked flask and heat to 60°C with mechanical stirring under N2 atmosphere. Then slowly drip a mixture of 400g of castor oil polyol and 76g of 2-acetylcitrate tributyl ester into the flask, and control the dripping speed to 1h. The temperature is kept constant at 80°C for 6h under nitrogen protection. When the NCO value does not change, cool to room temperature, discharge, and obtain a light yellow transparent polyurethane prepolymer, which is placed in a dry nitrogen sealed container for standby use.
[0031] 2. Preparation of two-component polyurethane adhesive
[0032] (1) 7 g of polytetrahydrofuran diol, 25 g of polyaspartic acid ester resin, 1 g of KH-792, and 67 g of alumina and boron nitride compound (the mass ratio of the two is 1:1) are placed in a stirring kettle and vacuumed and stirred for 1.5 h, with the mixing temperature being ≤60° C. and the vacuum degree being -0.08-0.09 MPa, to obtain component A;
[0033] (2) 32 g of polyurethane prepolymer and 68 g of a composite of aluminum oxide and boron nitride (the mass ratio of the two is 1:1) are placed in a stirring kettle, and vacuum stirred for 1.5 h at a mixing temperature of ≤50°C and a vacuum degree of -0.08-0.09 MPa to obtain component B.
[0034] Example 2
[0035] Preparation of an environmentally friendly two-component polyurethane thermal conductive structural adhesive:
[0036] 1. The preparation of polyurethane prepolymer is the same as in Example 1.
[0037] 2. Preparation of two-component polyurethane adhesive
[0038] (1) 10 g of polytetrahydrofuran diol, 30 g of polyaspartic acid ester resin, 2 g of KH-792, and 60 g of alumina and boron nitride compound (the mass ratio of the two is 1:1) are placed in a stirring kettle and vacuumed and stirred for 1.5 h, with the mixing temperature being ≤60° C. and the vacuum degree being -0.08-0.09 MPa, to obtain component A;
[0039] (2) 40 g of polyurethane prepolymer and 60 g of a composite of aluminum oxide and boron nitride (the mass ratio of the two is 1:1) are placed in a stirring kettle, and vacuum stirred for 1.5 h at a mixing temperature of ≤50°C and a vacuum degree of -0.08-0.09 MPa to obtain component B.
[0040] Example 3
[0041] Preparation of an environmentally friendly two-component polyurethane thermal conductive structural adhesive:
[0042] 1. Preparation of polyurethane prepolymer as in Example 1;
[0043] 2. Preparation of two-component polyurethane adhesive
[0044] (1) 6 g of polytetrahydrofuran diol, 27 g of polyaspartic acid ester resin, 1.5 g of KH-792, and 66 g of alumina boron nitride compound (the mass ratio of the two is 1:1) are placed in a stirring kettle and vacuumed and stirred for 1.5 h, with the mixing temperature being ≤ 60° C. and the vacuum degree being -0.08-0.09 MPa, to obtain component A;
[0045] (2) 35 g of polyurethane prepolymer and 65 g of aluminum oxide boron nitride compound (the mass ratio of the two is 1:1) are placed in a stirring kettle, and vacuum stirred for 1.5 hours at a mixing temperature of ≤50°C and a vacuum degree of -0.08-0.09 MPa to obtain component B.
[0046] Comparative Example 1
[0047] Preparation of an environmentally friendly two-component polyurethane thermal conductive structural adhesive:
[0048] 1. The preparation of polyurethane prepolymer is the same as in Example 1;
[0049] 2. Preparation of two-component polyurethane adhesive
[0050] (1) 13 g of polytetrahydrofuran diol, 14 g of polyaspartic acid ester resin, 1 g of KH-550, and 73 g of alumina were placed in a stirred kettle and vacuumed and stirred for 1.5 h at a mixing temperature of ≤60° C. and a vacuum degree of −0.08-0.09 MPa to obtain component A;
[0051] (1) 28 g of polyurethane prepolymer and 72 g of aluminum oxide were placed in a stirring kettle, and the mixture was stirred under vacuum for 1.5 h at a mixing temperature of ≤50° C. and a vacuum degree of -0.08-0.09 MPa to obtain component B.
[0052] Comparative Example 2
[0053] Preparation of an environmentally friendly two-component polyurethane thermal conductive structural adhesive:
[0054] 1. Preparation of polyurethane prepolymer as in Example 1;
[0055] 2. Preparation of two-component polyurethane adhesive
[0056] (1) 4 g of polyoxypropylene glycol, 33 g of polyaspartic acid resin, 1.5 g of KH-570, and 63 g of zinc oxide were placed in a stirred kettle and vacuumed and stirred for 1.5 h at a mixing temperature of ≤60° C. and a vacuum degree of -0.08-0.09 MPa to obtain component A;
[0057] (2) 26 g of polyurethane prepolymer and 74 g of zinc oxide were placed in a stirring kettle, and the mixture was stirred under vacuum for 1.5 h at a mixing temperature of ≤50° C. and a vacuum degree of -0.08-0.09 MPa to obtain component B.
[0058] Comparative Example 3
[0059] Preparation of an environmentally friendly two-component polyurethane thermal conductive structural adhesive:
[0060] 1. The preparation of polyurethane prepolymer is the same as in Example 1;
[0061] 2. Preparation of two-component polyurethane adhesive
[0062] (1) 17 g of polyoxypropylene glycol, 11 g of polyaspartic acid resin, 1.5 g of KH-560, and 72 g of boron nitride were placed in a stirred kettle and vacuumed and stirred for 1.5 h at a mixing temperature of ≤60° C. and a vacuum degree of -0.08-0.09 MPa to obtain component A;
[0063] (2) 43 g of polyurethane prepolymer and 57 g of boron nitride were placed in a stirring kettle, and the mixture was stirred under vacuum for 1.5 h at a mixing temperature of ≤50° C. and a vacuum degree of -0.08-0.09 MPa to obtain component B.
[0064] test
[0065] The thermally conductive structural adhesives prepared in the examples and comparative examples were subjected to the following performance tests, and the test results are shown in Table 1.
[0066] 1. Mechanical properties test
[0067] GB / T7124-2008 Determination of tensile shear strength of adhesives;
[0068] GB / T7314-2017 Determination of tensile strength of adhesives.
[0069] 2. Thermal conductivity test
[0070] ASTM D5470 Thermal conductivity test of non-metallic materials such as thermal conductive adhesives.
[0071] 3. Aging resistance test
[0072] At a temperature of 85°C and a humidity of 85%, a 1000h aging test was performed according to the above mechanical properties test standards.
[0073] Table 1. Comparison of test data of embodiments and comparative examples
[0074] name Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Shear strength / MPa 16.0 15.2 15.5 11.2 11.9 12.5 Tensile strength / Mpa 10.0 9.3 9.7 7.2 7.6 7.9 Thermal conductivity / W / m·K 1.25 1.20 1.22 1.23 1.14 1.10 Aging 1000h shear strength / MPa 15.1 14.3 14.4 7.4 7.6 7.9 Aging 1000h tensile strength / Mpa 9.3 8.5 8.9 5.1 5.3 5.6
[0075] As can be seen from the test results in Table 1, the two-component polyurethane adhesive in the embodiment of the present invention has excellent thermal conductivity and mechanical properties, and can maintain a good bonding and sealing effect during long-term use.
[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An environmentally friendly two-component polyurethane thermally conductive structural adhesive, characterized in that: The composition comprises the following components in parts by weight: Component A: 5-10 parts of polyether diol, 15-30 parts of polyaspartic acid ester resin, 1-2 parts of silane coupling agent, 60-70 parts of thermal conductive filler; Component B: 30-40 parts of polyurethane prepolymer and 60-70 parts of thermal conductive filler; the polyurethane prepolymer is a polymer with NCO terminal; The volume ratio of the A component to the B component is 1:
1.
2. The environmentally friendly two-component polyurethane thermally conductive structural adhesive according to claim 1, characterized in that: The polyurethane prepolymer is prepared from the following components in parts by weight: 35-75 parts of bio-based polyol, 15-55 parts of diisocyanate, and 5-10 parts of plasticizer.
3. The environmentally friendly two-component polyurethane thermally conductive structural adhesive according to claim 2, characterized in that: The molar ratio of isocyanate groups to hydroxyl groups in the polyurethane prepolymer is 2.5-3.0:
1.
4. The environmentally friendly two-component polyurethane thermally conductive structural adhesive according to claim 2, characterized in that: The preparation method of the polyurethane prepolymer comprises the following steps: heating diisocyanate to 50-70° C. with mechanical stirring in a N2 atmosphere, slowly dripping a mixture of bio-based polyol and plasticizer, controlling the dripping time to be 0.8-1.2 h, reacting for 4-6 h under N2 protection at a temperature of 80-85° C., cooling to room temperature until the NCO value does not change, and obtaining a light yellow transparent polyurethane prepolymer.
5. The environmentally friendly two-component polyurethane thermally conductive structural adhesive according to claim 2, characterized in that: The bio-based polyol is at least one of castor oil polyol, soybean oil polyol, palm oil polyol and rapeseed oil polyol; the diisocyanate is at least one of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate; and the plasticizer is 2-acetylcitrate tributyl.
6. The environmentally friendly two-component polyurethane thermally conductive structural adhesive according to claim 1, characterized in that: The polyether diol is at least one of polyoxypropylene diol and polytetrahydrofuran diol.
7. The environmentally friendly two-component polyurethane thermally conductive structural adhesive according to claim 1, characterized in that: The polyether diol has a hydroxyl value of 50-500 mg KOH / g, an average hydroxyl molecular weight of 250-2000, and an acid value of less than 1; the polyaspartic acid ester resin has a molecular weight of 554-660 and an equivalent weight of 277-330 g / mol.
8. The environmentally friendly two-component polyurethane thermally conductive structural adhesive according to claim 1, characterized in that: The silane coupling agent is one of KH-550, KH-560, KH-570 and KH-792.
9. The environmentally friendly two-component polyurethane thermally conductive structural adhesive according to claim 1, characterized in that: The thermal conductive filler is at least one of aluminum oxide, magnesium oxide, zinc oxide, aluminum nitride, boron nitride, silicon carbide, and a composite of aluminum oxide and boron nitride.
10. A method for preparing the environmentally friendly two-component polyurethane thermally conductive structural adhesive according to any one of claims 1 to 9, characterized in that: The steps include: (1) placing polyether diol, polyaspartic acid ester resin, silane coupling agent and thermal conductive filler into a stirring kettle, evacuating and stirring for 1-2 hours at a mixing temperature of ≤60°C to obtain component A; (2) Put the polyurethane prepolymer and thermal conductive filler into a stirring kettle, vacuum and stir for 1-2 hours, with the mixing temperature ≤50°C, to obtain component B.
Citation Information
Patent Citations
Preparation method of aspartate pouring sealant
CN107987782A
Polyaspartic acid ester polyurea-based repairing material for repairing polyurethane foam of automobile instrument board, and preparation method and repairing method thereof
CN110845685A
Preparation method of elastic polyaspartic acid ester pouring sealant and product thereof
CN113122175A
High-thermal-conductivity polyurethane, and preparation method and application thereof
CN115572363A
Solvent-free bio-based polyurethane heat-conducting structural adhesive and preparation method thereof
CN117801763A
Cited By
Wide-temperature-range polyurethane material with excellent adhesive property and preparation method of wide-temperature-range polyurethane material
CN120923715A